Pengaruh Motivasi Kerja Guru dan Kepemimpinan Kepala Sekolah terhadap Kinerja Guru - Mahendra Mahendra; Yasir Arafat; Andi Arif Setiawan (Yayasan Darusssalam Bengkulu, 2020)
This study determined the effect of teacher work motivation and principal leadership on teacher performance. This research uses quantitative methods with correlational research type. This research is a population study with 61 research subjects, namely teachers of public elementary schools in Gugus 03 Muara Telang. The data collection technique used a questionnaire. Data were analyzed using correlation analysis techniques and multiple linear regression. The results showed that: (1) teacher work motivation has a positive and significant effect on the performance of teachers at SD Negeri Gugus 03, Muara Telang District; (2) Principal leadership has a positive and significant effect on teacher performance at SD Negeri Gugus 03, Muara Telang District; (3) Teacher work motivation and principal leadership together have a positive and significant effect on teacher performance at SD Negeri Gugus 03, Muara Telang District.